Application of Marketing Communication Tools in Small and Medium Enterprises. Results of Regional Research - Małgorzata Adamska (Barometr Regionalny)
This paper aims to investigate the application of different types of communications forms and tools in the context of client capital management and development of the client lifetime value in the sector of small and medium enterprises. The research method was a questionnaire survey using computer-aided telephone interviews (CATI), on a group of 383 small and medium-sized enterprises from the Opolskie Voivodship. This research illustrates the use of diverse forms and tools by diverse members of the SME sector. More importantly, this research prepares conclusions for future development of communication as a main stimulator of increasing client lifetime value. The findings show that the small and medium enterprises in Opolskie Voivodship are aware of the need to use a variety of tools to communicate with clients. The tools are diverse and have a different degree of contact intensity, which effectively contributes to the involvement of clients in the relationship with the company’s offer. In the future the SME sector should develop and diversify channels of communication with client capital. For modern enterprises, the most important thing will be constant development of the client’s lifetime value.